Rational mix design of lightweight concrete for optimum strength - Th. Dawood, Eethar; Ramli, Mahyuddin (2008)
In this study, structural lightweight concretes produced by Coarse lightweight Crushed brick and Fine light weight crushed brick (CLWA & FLWA) were investigated. Compressive strength and Density of the concretes were determined in order to make some procedures for mix design of lightweight concrete. In producing the mixtures, superplasticizer (SP) was used in 1% of cement weight to improve the workability. In conclusion, the fresh density of lightweight concrete with fully replacement of sand by FLWA was decreased by about 200 kg/m3 compared with the mix of fully sand as fine aggregate with no reduction for the compressive strength. It was concluded also that the voids between fine aggregate particles (sand + FLWA) affect on the compressive strength of the mix especially at 28 days. This study suggests inclusion of the voids between fine aggregate particles as a significant factor affects on the compressive strength of lightweight concrete.